Dental and skeletal effects of combined headgear used alone or in association with rapid maxillary expansion - Farret,Milton Meri Benitez (2015)
Objective: The aim of this study was to assess the effects of combined headgear used alone or in association with rapid maxillary expansion, as the first step for Class II malocclusion treatment.Methods:The sample comprised 61 patients divided into three groups: Group 1, combined headgear (CH); Group 2, CH + rapid maxillary expansion (CH + RME); and Group 3, control (CG). In Group 1, patients were treated with combined headgear until Class I molar relationship was achieved. In Group 2, the protocol for headgear was the same; however, patients were previously subject to rapid maxillary expansion.Results:Results showed distal displacement of maxillary molars for both experimental groups (p < 0.001), with distal tipping only in Group 1 (CH) (p < 0.001). There was restriction of forward maxillary growth in Group 2 (CH + RME) (p < 0.05) and clockwise rotation of the maxilla in Group 1 (CH) (p < 0.05).Conclusion: Based on the results, it is possible to suggest that treatment with both protocols was efficient; however, results were more significant for Group 2 (CH + RME) with less side effects.